Filamentary flow and magnetic geometry in evolving cluster-forming molecular cloud clumps - Klassen, Mikhail; Pudritz, Ralph E.; Kirk, Helen (Monthly notices of the Royal Astronomical Society, 2017)
We present an analysis of the relationship between the orientation of magnetic fields and filaments that form in 3D magnetohydrodynamic simulations of cluster-forming, turbulent molecular cloud clumps. We examine simulated cloud clumps with size scales of L ∼ 2-4 pc and densities of n ∼ 400-1000 cm−3 with Alfvén Mach numbers near unity. We simulated two cloud clumps of different masses, one in virial equilibrium, the other strongly gravitationally bound, but with the same initial turbulent velocity field and similar mass-to-flux ratio. We apply various techniques to analyse the filamentary and magnetic structure of the resulting cloud, including the DisPerSE filament-finding algorithm in 3D. The largest structure that forms is a 1-2 parsec-long filament, with smaller connecting sub-filaments. We find that our simulated clouds, wherein magnetic forces and turbulence are comparable, coherent orientation of the magnetic field depends on the virial parameter. Sub-virial clumps undergo strong gravitational collapse and magnetic field lines are dragged with the accretion flow. We see evidence of filament-aligned flow and accretion flow on to the filament in the sub-virial cloud. Magnetic fields oriented more parallel in the sub-virial cloud and more perpendicular in the denser, marginally bound cloud. Radiative feedback from a 16 M⊙ star forming in a cluster in one of our simulation's ultimately results in the destruction of the main filament, the formation of an H ii region, and the sweeping up of magnetic fields within an expanding shell at the edges of the H ii region.